PENGALAMAN MANAJER KEUANGAN DALAM MENGHADAPI KETIDAKPASTIAN EKONOMI: PERSPEKTIF AKUNTANSI MANAJEMEN - Ratnawati, Dwi Puji (PT. Samudra Solusi Profesional, 2026)
This study aims to analyze the experiences of financial managers in dealing with economic uncertainty from a management accounting perspective. Economic uncertainty, characterized by macroeconomic fluctuations, market volatility, and changes in government policies, requires companies to strengthen their planning systems, cost control mechanisms, and risk management practices. This study employs a qualitative approach using in-depth interviews with three financial managers from the manufacturing, service, and trade sectors. The data were analyzed using thematic analysis techniques to identify the strategies implemented in response to unstable economic conditions. The findings indicate that financial managers enhance scenario-based planning, implement stricter cost control measures, and improve liquidity and risk management through the support of management accounting systems. Furthermore, professional experience plays a crucial role in integrating quantitative data with strategic intuition, resulting in more adaptive and comprehensive decision-making. This study emphasizes that the effectiveness of management accounting systems and the quality of human resources are key factors in maintaining organizational resilience amid economic uncertainty.